(untitled) (Research, Society and Development, 2023)
Objective: to evaluate the role of nursing in the face of the COVID-19 pandemic and determine the impacts suffered by professionals in the face of this new scenario. Methodology: integrative review with a survey in the following databases, virtual health library (VHL), nursing database (BENDF) and SciELO. Results: the final sample of this review consisted of 16 articles selected by the inclusion criteria previously established, evidenced on the role of the nursing professional in the pandemic, emphasizing the difficulties that are imposed and the exposure in which they find themselves in the aforementioned scenario. Conclusion: in the end, it is evident that the role of nursing is of paramount importance in the context of customer care; however, it needs more help to outline and support systematization with better quality managing to meet the needs satisfactorily, without worrying about the challenges and uncertainties that come along in the scope of work.